The health and socioeconomic impacts of major multi-sport events: systematic review (1978-2008). (20th May 2010) - McCartney, Gerry; Thomas, Sian; Thomson, Hilary; Scott, John; Hamilton, Val; Hanlon, Phil; Morrison, David S; Bond, Lyndal
Abstract : Objective To assess the effects of major multi-sport events on health and socioeconomic determinants of health in the population of the city hosting the event. Design Systematic review. Data sources We searched the following sources without language restrictions for papers published between 1978 and 2008: Applied Social Science Index and Abstracts (ASSIA), British Humanities Index (BHI), Cochrane database of systematic reviews, Econlit database, Embase, Education Resources Information Center (ERIC) database, Health Management Information Consortium (HMIC) database, International Bibliography of the Social Sciences (IBSS), Medline, PreMedline, PsycINFO, Sociological Abstracts, Sportdiscus, Web of Knowledge, Worldwide Political Science Abstracts, and the grey literature. Review methods Studies of any design that assessed the health and socioeconomic impacts of major multi-sport events on the host population were included. We excluded studies that used exclusively estimated data rather than actual data, that investigated host population support for an event or media portrayals of host cities, or that described new physical infrastructure. Studies were selected and critically appraised by two independent reviewers. Results Fifty four studies were included. Study quality was poor, with 69% of studies using a repeat cross-sectional design and 85% of quantitative studies assessed as being below 2+ on the Health Development Agency appraisal scale, often because of a lack of comparison group. Five studies, each with a high risk of bias, reported health related outcomes, which were suicide, paediatric health service demand, presentations for asthma in children (two studies), and problems related to illicit drug use. Overall, the data did not indicate clear negative or positive health impacts of major multi-sport events on host populations. The most frequently reported outcomes were economic outcomes (18 studies). The outcomes used were similar enough to allow us to perform a narrative synthesis, but the overall impact of major multi-sport events on economic growth and employment was unclear. Two thirds of the economic studies reported increased economic growth or employment immediately after the event, but all these studies used some estimated data in their models, failed to account for opportunity costs, or examined only short term effects. Outcomes for transport were also similar enough to allow synthesis of six of the eight studies, which showed that event related interventions—including restricted car use and public transport promotion—were associated with significant short term reductions in traffic volume, congestion, or pollution in four out of five cities. Conclusions The available evidence is not sufficient to confirm or refute expectations about the health or socioeconomic benefits for the host population of previous major multi-sport events. Future events such as the 2012 Olympic Games and Paralympic Games, or the 2014 Commonwealth Games, cannot be expected to automatically provide benefits. Until decision makers include robust, long term evaluations as part of their design and implementation of events, it is unclear how the costs of major multi-sport events can be justified in terms of benefits to the host population.